Evaluation of the phytochemical content, antioxidant activity and antimicrobial properties of mountain tea (Sideritis syriaca) decoction - Vlasios Goulas; Vassiliki Exarchou; Loukas Kanetis; Ioannis P. Gerothanassis (Journal of Functional Foods, 2014)
Mountain tea is an easily available, low cost herb consumed on a daily basis, and is believed to contain bioactive phytochemicals. The evaluation of functional properties and bioactive composition of the decoction is essential for its exploitation as a health-promoting beverage. The antimicrobial properties of Sideritis syriaca decoction were demonstrated a considerable antimicrobial activity against Staphylococcus aureus. In addition, its antioxidant activity was indicated from different in vitro assays. HPLC–SPE–NMR technique was then optimized to analyze its phytochemical content. The major phytochemicals were found to be hypoelatin and isoscutellarein diglucosides, while the phenylpropanoids such as verbascoside, martynoside, lavandulifolioside, and chlorogenic acid were also identified by combining NMR, UV and MS data. Finally, the on-line HPLC–DPPH demonstrated that the antioxidant activity of the decoction was mainly due to its flavonoid content. Overall, mountain tea decoction can be considered as a health-promoting beverage with functional properties that deserve further exploitation.